Algorithms of oppression : how search engines reinforce racism - Noble, Safiya Umoja (New York University Press, 2018)
"In Algorithms of Oppression, Safiya Umoja Noble challenges the idea that search engines like Google offer an equal playing field for all forms of ideas, identities, and activities. Data discrimination is a real social problem. Noble argues that the combination of private interests in promoting certain sites, along with the near-monopoly status of a relatively small number of Internet search engines, leads to a biased set of search algorithms that discriminate against people of color, especially women of color.